Non-invasive Assessment of Neurovascular Coupling After Aneurysmal Subarachnoid Hemorrhage: A Prospective Observational Trial Using Retinal Vessel Analysis - Albanna, Walid; Conzen, Catharina; Weiss, Miriam; Seyfried, Katharina; Kotliar, Konstantin; Schmidt, Tobias Philip; Kuerten, David; Hescheler, Jürgen; Bruecken, Anne; Schmidt-Trucksäss, Arno; Neumaier, Felix; Wiesmann, Martin; et al. (Frontiers in Neurology, 2021)
Objective: Delayed cerebral ischemia (DCI) is a common complication after aneurysmal subarachnoid hemorrhage (aSAH) and can lead to infarction and poor clinical outcome. The underlying mechanisms are still incompletely understood, but animal models indicate that vasoactive metabolites and inflammatory cytokines produced within the subarachnoid space may progressively impair and partially invert neurovascular coupling (NVC) in the brain. Because cerebral and retinal microvasculature are governed by comparable regulatory mechanisms and may be connected by perivascular pathways, retinal vascular changes are increasingly recognized as a potential surrogate for altered NVC in the brain. Here, we used non-invasive retinal vessel analysis (RVA) to assess microvascular function in aSAH patients at different times after the ictus. Methods: Static and dynamic RVA were performed using a Retinal Vessel Analyzer (IMEDOS Systems GmbH, Jena) in 70 aSAH patients during the early (d0−4), critical (d5−15), late (d16−23) phase, and at follow-up (f/u > 6 weeks) after the ictus. For comparison, an age-matched cohort of 42 healthy subjects was also included in the study. Vessel diameters were quantified in terms of the central retinal arterial and venous equivalent (CRAE, CRVE) and the retinal arterio-venous-ratio (AVR). Vessel responses to flicker light excitation (FLE) were quantified by recording the maximum arterial and venous dilation (MAD, MVD), the time to 30% and 100% of maximum dilation (tMAD30, tMVD30; tMAD, tMVD, resp.), and the arterial and venous area under the curve (AUCart, AUCven) during the FLE. For subgroup analyses, patients were stratified according to the development of DCI and clinical outcomes after 12 months. Results: Vessel diameter (CRAE, CRVE) was significantly smaller in aSAH patients and showed little change throughout the whole observation period (p < 0.0001 vs. control for all time periods examined). In addition, aSAH patients exhibited impaired arterial but not venous responses to FLE, as reflected in a significantly lower MAD [2.2 (1.0–3.2)% vs. 3.6 (2.6–5.6)% in control subjects, p = 0.0016] and AUCart [21.5 (9.4–35.8)%*s vs. 51.4 (32.5–69.7)%*s in control subjects, p = 0.0001] on d0−4. However, gradual recovery was observed during the first 3 weeks, with close to normal levels at follow-up, when MAD and AUCart amounted to 3.0 [2.0–5.0]% (p = 0.141 vs. control, p = 0.0321 vs. d5−15) and 44.5 [23.2–61.1]%*s (p = 0.138 vs. control, p < 0.01 vs. d0−4 & d5−15). Finally, patients with clinical deterioration (DCI) showed opposite changes in the kinetics of arterial responses during early and late phase, as reflected in a significantly lower tMAD30 on d0−4 [4.0 (3.0–6.8) s vs. 7.0 (5.0–8.0) s in patients without DCI, p = 0.022) and a significantly higher tMAD on d16−23 (24.0 (21.0–29.3) s vs. 18.0 (14.0–21.0) s in patients without DCI, p = 0.017]. Conclusion: Our findings confirm and extend previous observations that aSAH results in sustained impairments of NVC in the retina. DCI may be associated with characteristic changes in the kinetics of retinal arterial responses. However, further studies will be required to determine their clinical implications and to assess if they can be used to identify patients at risk of developing DCI. Trial Registration:ClinicalTrials.gov Identifier: NCT04094155.